Atmospheric corrosion protection method for corroded steel members using sacrificial anode of Al-based alloy. (20th February 2020) - Yang, Muye; Kainuma, Shigenobu; Ishihara, Shuji; Kaneko, Akira; Yamauchi, Takao
Highlights: A corrosion protection system was developed for corroded steel members in atmospheric environment. Durability of the system was verified through atmospheric exposure test on a real-life bridge. Effect of activator elements (Zn and In) on the galvanic coupling characteristics was indicated. Corrosion kinetic model and the change in rust under cathodic protection were investigated. Abstract: This paper proposes a new cathodic protection (CP) system, for steel members vulnerable to corrosion damage in the atmospheric environment. To ensure that this system is suitable for the atmospheric environment, an absorbent fiber sheet is considered as the electrolyte carrier. The independent performance of each component and the combined effectiveness of the CP system are studied by conducting a water absorption test and electrochemical tests using various concentrated NaCl solutions. In addition, the effects of the activator elements (Zn and In) on the galvanic coupling characteristics are investigated through an indoor test. The system durability is verified in an aggressive atmospheric environment, where CP continues for 15 months effectively without any manual intervention. In practice, the CP system's effectiveness is reflected in the continuous anti-corrosion current as well as the change in the reducing environment at the steel surface, but a change in the local environment at the steel interface is more likely to restore passivity. Finally, by modeling the corrosion reactions and variations in a rust film under wet-dry cycles, we suggest that the steel members of a roughly cleaned surface can be protected by the CP system even in the presence of residual rust.